Answer:
(2,-2) is your answer
Step-by-step explanation:
The equation given in the question is
3(3x - 1) + 2(3 - x) = 0
9x - 3 + 6 - 3x = 0
6x + 3 = 0
6x = - 3
x = - (3/6)
= - (1/2)
So the value of x as has been determined above is -1/2. I hope the procedure is clear enough for you to understand.<span>You can
always use this method for solving problems that are similar in type without
requiring any help from outside. </span>
Answer:
Check out the image below!
Step-by-step explanation:
38 (average) - 29.777 (this year) = 8.223 inches less this year than the average year.
Answer:
32/4
simplified is 8/1
Step-by-step explanation: